Fractionated busulfan myeloablative conditioning improves survival in older patients with acute myeloid leukemia and myelodysplastic syndrome. Issue 10 (20th January 2021) - Oran, Betül; Saliba, Rima M.; Mehta, Rohtesh S.; Alousi, Amin M.; Marin, David; Valdez, Ben C.; Chen, Julianne; Bashir, Qaiser; Ciurea, Stefan O.; Olson, Amanda L.; Hosing, Chitra; Kebriaei, Partow; et al.
Abstract : Background: A myeloablative conditioning regimen can be safely given to older patients and those with comorbidities without increasing nonrelapse mortality (NRM) by fractionating the dose of intravenous busulfan. How this approach compares in efficacy with traditional, nonfractionated, lower dose regimens is unknown. Methods: Outcomes were compared in patients with acute myeloid leukemia (AML) or myelodysplastic syndrome who received either myeloablative, fractionated busulfan (f‐Bu) dosed to achieve an area under the curve of 20, 000 μmol per minute (f‐Bu20K) over 2 weeks (n = 84) or a standard, nonfractionated, lower busulfan dose regimen of 16, 000 μmol per minute (Bu16K) over 4 days (n = 78). Both groups also received fludarabine 40 mg/m 2 intravenously for 4 days. Graft‐versus‐host disease prophylaxis was tacrolimus and methotrexate. Patients in the Bu16K group who had unrelated donors also received antithymocyte globulin. The primary endpoint was progression‐free survival. Results: Roughly one‐half of the patients were aged >65 years, approximately 40% had poor‐risk cytogenetics, approximately 40% of those with AML were not in complete remission, and approximately 40% had a comorbidity index >3. At 2 years, progression‐free survival was significantly improved in the f‐Bu20K group compared with the Bu16K group (45% vs 24%, respectively; hazard ratio [HR], 0.6; 95% CI, 0.4‐0.8; P = .004). This was because of a significant reduction in progression (34% vs 59%, respectively; HR, 0.5; 95% CI, 0.3‐0.8; P = .003) without any increase in NRM (21% vs 15%, respectively; HR, 1.4; 95% CI, 0.7‐3; P = .3), which resulted in improved overall survival (51% vs 31%, respectively; HR, 0.6; 95% CI, 0.3‐0.9; P = .01). Conclusions: A myeloablative, fractionated busulfan regimen reduces relapse and improves survival without increasing NRM in older patients with AML and myelodysplastic syndrome. Abstract : A myeloablative, fractionated regimen of busulfan reduces relapse and improves survival without increasing nonrelapse mortality in older patients with acute myeloid leukemia and myelodysplastic syndrome.